Competição bancária e estabilidade financeira: há trade-off no caso brasileiro? - Jensen, Letícia Penhalver [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Embora o referencial teórico da relação entre estabilidade financeira e competição bancária seja vasto, não existe consenso na literatura. O objetivo principal deste trabalho é contribuir para a melhor identificação dos padrões dessa relação. Através de uma análise em nível de empresa, ao buscar evidenciar as características microeconômicas dos riscos dos bancos, identificamos quatro modelos que formam estimados por dados em painel. Os resultados obtidos não evidenciam que uma maior concentração de mercado melhora a estabilidade financeira.

Even though the theoretical framework of the trade-off between financial stability and banking competition is vast, there is no agreement in the literature. The main goal of this work is to contribute to the literature in order to a better explanation of this relationship. Through an analysis at a firm level, in highlighting the microeconomic aspects of bank risks , we have identified four models all estimated by panel data. The results did not show that a rise in the market concentration improves financial stability.
Bank competition and financial stability: is there a trade-off in the Brazilian case?
Keywords: Estabilidade financeira; Risco bancário; Painel com efeitos fixos; Financial stability; Banking risks; Panel with fixed effects